Pengaruh Thin Capitalization dan Sales Growth terhadap Tax Avoidance - Rahmahwati, Fitri; Sahara, Lia Ira (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the impact of thin capitalization and sales growth on corporate tax avoidance, an issue that poses a significant challenge for tax authorities in enhancing state revenue. The research focuses on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using purposive sampling, 32 firms were selected, resulting in 160 firm-year observations. A quantitative approach was applied, employing panel data regression analysis through EViews 13 software to test the hypotheses. The results reveal that thin capitalization has a significant negative effect on tax avoidance, suggesting that companies with higher debt-to-equity ratios are less likely to engage in aggressive tax strategies. Conversely, sales growth shows a significant positive effect on tax avoidance, indicating that firms with growing revenue are more inclined to reduce tax burdens through legal means. Furthermore, the findings confirm that both variables jointly influence tax avoidance behavior. These results highlight the importance of internal financial strategies in shaping corporate tax compliance and provide valuable input for policymakers to strengthen regulations aimed at limiting tax avoidance practices.